Experimental investigation of a reinforced soil retaining wall with a flexible geogrid-wrapped ecological bag facing. Issue 1 (February 2021) - Duan, Junyi; Yang, Guolin; Lin, Yuliang; Cheng, Xinting; Dai, Zhihao
Abstract: This paper presented a field study of the reinforced soil wall (RSW) with a geogrid wrap-around facing. In addition to the conventional monitoring content, the strain of the face-wrapping geogrid, which was neglected in most previous studies, was monitored during the construction process. The positional relationship between the maximum vertical earth pressure and horizontally laid geogrid strain was revealed by using the proposed oblique dragging effect. It was found that the strain on the face-wrapping geogrid occurred mainly in the early stage of construction. The oblique dragging effect existing in the flexible RSWs increased the vertical earth pressure and changed its distribution law, resulting in the position of the maximum vertical soil pressure appearing behind the position of the maximum horizontally laid geogrid strain. The horizontal earth pressure at different positions behind the wall was obviously lower than the theoretical result by using Rankine's theory. Also, a modified 0.3 H method (where H refers to the wall height) was presented to account for the slope of the wall face, which could be used to determine the potential sliding surfaces for single-stage RSWs and two-tier RSWs with small offset. Highlights: A field test of the reinforced soil wall (RSW) with a geogrid wrap-around facing was presented. The positional relationship between the maximum vertical earth pressure and horizontally laid geogrid strain was revealed. The oblique dragging effect resulted in the change of the distribution characteristics of vertical earth pressure. A modified 0.3H method taking account of the inclination of the wall face was presented.